KEBIJAKAN HUKUM PIDANA TERHADAP PELAKU PERUNDUNGAN (BULLYING) ANAK DIBAWAH UMUR - Siti Iba Iga Farida; Rochmani Rochmani (Jurnal Ilmiah Dinamika Hukum, 2020)
The biggest problem for children who are faced with the law is because of Law no. 3 of 1997 regarding Juvenile Court is no longer relevant, both from the juridical, philosophical and sociological aspects. This law does not provide the right solution for the handling of children as children in conflict with the law. Children who are in conflict with the law that is resolved in court, result in mental and psychological pressure on the child who is in conflict with the law, thus disturbing the child's development and development. Thus, there is a need for a criminal law policy in handling bullying. The research method used in this research is juridical empirical by looking at the facts that exist in practice in the field. The research objective is to explain policies in law enforcement against child bullies. Settlement of the criminal law for bullying offenders against student victims of violence at school has not been going well because bullying has not been regulated in a law that specifically regulates it. Keywords : children, underage, criminal law, policy, bullying.